Trends in Anterior Cruciate Ligament Repair: A Bibliometric and Visualized Analysis. Issue 10 (25th October 2022) - Li, Jinfei; Rothrauff, Benjamin; Chen, Shuyi; Zhao, Shuying; Wu, Zhaoxi; Chen, Qi; He, Jinshen
Background: Bibliometrics is a methodology that measures the scientific output of an author, institution, or country. Visualized analysis is the transformation of data into visible form by software, highlighting important features, including commonalities and anomalies, allowing users to easily and quickly perceive significant aspects of their data. Purpose: To conduct a bibliometric analysis of the literature on anterior cruciate ligament (ACL) repair, with visualization of trends, in order to identify the areas of interest and the primary researchers involved in ACL repair. Study Design: Cross-sectional study. Methods: The PubMed database was queried on April 14, 2022, for publications that reported on ACL repair from 1960 onward. The initial search resulted in 1392 publications. Filter settings were applied to remove publications with weak correlation, such as those on meniscal repair and ACL reconstruction. Publication information, citations, authors, commonly used terms, and affiliated institutions and countries were analyzed by VOSviewer and Python. Results: A total of 553 articles were included for analysis. Three techniques were visualized: bridge-enhanced ACL repair, internal brace, and dynamic intraligamentary stabilization. The most published authors were Martha Murray (51 articles), Gregory Difelice (35 articles), and Braden Fleming (31 articles). The most cited article was "Collagen–Platelet Rich Plasma Hydrogel Enhances Primary Repair of the Porcine Anterior Cruciate Ligament" by Murray et al. The journals with the most publications on ACL repair were the American Journal of Sports Medicine (n = 49); Knee Surgery, Sports Traumatology, Arthroscopy (n = 49); and Arthroscopy (n = 48). The top 3 institutions by publication number were the Hospital for Special Surgery (n = 51), Boston Children's Hospital (n = 49), and Brown University (n = 31), with the most publications coming from the United States (n = 242), Germany (n = 83), and the United Kingdom (n = 47). Conclusion: The results demonstrate that the research on ACL repair comes from a small number of authors and corresponding institutions; the top sports medicine journals and the developed countries have an interest in this topic.